2021
DOI: 10.1186/s13690-021-00739-5
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual and reproductive health knowledge, sexual attitudes, and sexual behaviour of university students: Findings of a Beijing-Based Survey in 2010-2011

Abstract: Background Although several studies have attempted investigating sex-related knowledge, attitudes, and practices among young people in China, deeper insights were still needed to further understand how this population could be supported to make healthy and safe sexual choices. Against this background, this study used a large set of secondary data to examine associations among sexual and reproductive health (SRH) knowledge, sexual attitudes, and sexual behaviour. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
1
4
0
4
Order By: Relevance
“…The general level of knowledge was low among young people regardless of gender as in several other studies (Brunelli et al, 2022;Ivanova et al, 2018). Similar to some studies (Guan et al, 2021;Vongxay et al, 2019) we found that most young people (54.4%) were unfamiliar with reproductive health, abortion and sexual and reproductive rights, but this proportion is slightly higher than that reported by Ayalew et al (2019) in Ethiopia, where the study population was exclusively students. Very few young people had good knowledge of contraceptive method (18.4%) and good knowledge of STIs/ HIV/ AIDS (15.4%) and their transmission routes, as found by other authors (Tanabe et al, 2015;Okanlawon et al, 2010;Tanabe et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The general level of knowledge was low among young people regardless of gender as in several other studies (Brunelli et al, 2022;Ivanova et al, 2018). Similar to some studies (Guan et al, 2021;Vongxay et al, 2019) we found that most young people (54.4%) were unfamiliar with reproductive health, abortion and sexual and reproductive rights, but this proportion is slightly higher than that reported by Ayalew et al (2019) in Ethiopia, where the study population was exclusively students. Very few young people had good knowledge of contraceptive method (18.4%) and good knowledge of STIs/ HIV/ AIDS (15.4%) and their transmission routes, as found by other authors (Tanabe et al, 2015;Okanlawon et al, 2010;Tanabe et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted in China reported that sexual attitudes had a mediating effect on knowledge of risky sex and sexual behaviors among university students [33]. Prior studies reported that individuals with negative sexual attitudes were less likely to use condoms during sex than those with positive sexual attitudes [7] and having a positive attitude toward implementing safe sexual behaviors was associated with actual safe sexual behaviors in women with economic decision-making autonomy [34].…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that one's reproductive health knowledge does not have any correlation with personal sexual attitude. According to Uluc et al (2019), as cited by the results of Guan (2021), there are no meaningful relationships between knowledge, behavior, and attitude. Undergraduates tended to have more sources and categories of sexual reproductive knowledge, less knowledge about the safety period and using condoms, but a more positive attitude toward unmarried sex.…”
Section: Relationship Between Sexual Health Knowledge and Sexual Atti...mentioning
confidence: 99%